The Relationship Between the Level of Anxiety of Postpartum Mothers and Breastfeeding at The Srikandi Husada Clinic, Bae District, Kudus Regency In 2025 - Meylani Kusuma Dewi; Diah Andriani Kusumastuti; Ika Tristanti (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aimed to determine the relationship between the anxiety level of postpartum mothers and breastfeeding practices at Srikandi Husada Clinic, Bae District, Kudus Regency, in 2025. It was hypothesized that higher maternal anxiety would be associated with less optimal breastfeeding practices. Research Method: This study used a quantitative analytical design with a cross-sectional approach. The sample consisted of 32 postpartum mothers selected from postpartum visits at Srikandi Husada Clinic. Anxiety level was measured using the Hamilton Anxiety Rating Scale (HARS-A), while breastfeeding practice was assessed using a structured questionnaire. Data were analyzed using univariate analysis and Fisher’s Exact Test. Results and Discussion: Most respondents experienced mild anxiety (40.6%), followed by moderate anxiety (31.3%). In terms of breastfeeding, 53.1% of mothers practiced predominant breastfeeding, 37.5% partial breastfeeding, and 9.4% did not breastfeed. Bivariate analysis showed a significant relationship between postpartum maternal anxiety and breastfeeding practice (p < 0.001). Higher anxiety levels were associated with a lower tendency to provide optimal breastfeeding. Implications: These findings highlight the importance of maternal psychological support during the postpartum period to improve breastfeeding outcomes. Further studies are recommended to explore additional psychosocial and family-related factors influencing breastfeeding success.